Doping‐Induced Amorphization, Vacancy, and Gradient Energy Band in SnS2 Nanosheet Arrays for Improved Photoelectrochemical Water Splitting. Issue 20 (9th April 2019) - Meng, Linxing; Wang, Siyu; Cao, Fengren; Tian, Wei; Long, Run; Li, Liang
Abstract: Photoelectrochemical (PEC) water splitting is a promising strategy to convert solar energy into hydrogen fuel. However, the poor bulk charge‐separation ability and slow surface oxygen evolution reaction (OER) dynamics of photoelectrodes impede the performance. We construct In‐ and Zn/In‐doped SnS2 nanosheet arrays through a hydrothermal method. The doping induces the simultaneous formation of an amorphous layer, S vacancies, and a gradient energy band. This leads to elevated carrier concentrations, an increased number of surface‐reaction sites, accelerated surface‐OER kinetics, and an enhanced bulk‐carrier separation efficiency with a decreased recombination rate. This efficient doping strategy allows to manipulate the morphology, crystallinity, and band structure of photoelectrodes for an improved PEC performance. Abstract : Doped for performance : In‐ and Zn/In‐doped SnS2 nanosheet arrays are used as photoanodes for the photoelectrochemical splitting of water. The doping induces the formation of an amorphous overlayer and S vacancies on the nanosheet surface, as well as a gradient energy‐band distribution along the cross‐section of the nanosheet arrays. This leads to an increased performance in water splitting.